2010
DOI: 10.1007/s10463-010-0308-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the ratio of two scale parameters: a simple approach

Abstract: We describe a simple approach for estimating the ratio ρ = σ 2 /σ 1 of the scale parameters of two populations from a decision theoretic point of view. We show that if the loss function satisfies a certain condition, then the estimation of ρ reduces to separately estimating σ 2 and 1/σ 1 . This implies that the standard estimator of ρ can be improved by just employing an improved estimator of σ 2 or 1/σ 1 . Moreover, in the case where the loss function is convex in some function of its argument, we prove that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The dominance property given in Theorem 2.1 can be provided as a simple conclusion of Kubokawa and Srivastava (1996), Iliopoulos and Kourouklis (1999) and Bobotas, et al . (2012).…”
Section: General Dominance Results In Estimation Of Ratio Of Positivementioning
confidence: 99%
See 2 more Smart Citations
“…The dominance property given in Theorem 2.1 can be provided as a simple conclusion of Kubokawa and Srivastava (1996), Iliopoulos and Kourouklis (1999) and Bobotas, et al . (2012).…”
Section: General Dominance Results In Estimation Of Ratio Of Positivementioning
confidence: 99%
“…Thus, we could not answer whether the stronger dominance property holds or not for the quadratic loss. In stead ofρ * =θ * 2 /θ * 1 , Kubokawa (1994b) and Bobotas, et al . (2012) showed that the double shrinkage estimator of the formρ 2 .…”
Section: Remark 21 Theorems 21 and 22 Imply That The Crude Ratio Ementioning
confidence: 99%
See 1 more Smart Citation
“…Τέλος, στην περίπτωση του προβλήµατος εκτίµησης του λόγου των παραµέτρων κλίµακας δύο εκθετικών κατανοµών, οι Madi and Tsui (1990b) , ενώ η Ενότητα 3.5 αποτελεί µέρος της εργασίας Bobotas, Iliopoulos and Kourouklis (2009).…”
Section: βελτιωµένοι εκτιµητές για το λόγο παραµέτρων κλίµακαςunclassified